PERCOBAAN PEMUTIBAN TEPUNG SAGU (METROXYLON SP.) DENGAN KAPORIT - Abdul Hakim Lukman (Pusat Penelitian dan Pengembangan Hasil Hutan, 1991)
The effect of the bleaching of sago flour by calcium hypochlorite solution at several concentration levels (0; 1,5; 2,0; and 2,5 percent) and soaking time (30, 45, and 60 minutes) on sago flour quality were studied at the Forest Product Research and Development Centre Laboratory in Bogor. Results showed that unbleached sago flour when soaked for 60. minutes gave the highest yield (89.48 percent). At 1.5 percent hypochlorite concentration and 30 minutes soaking time, the proximate analysis including moisture, ash, fat, starch, protein and crude fiber contents are consecutively 9.34, 0. 5, 0.28, 87.60, 0.56, and 0. 74 percent. Application of 1.5 percent calcium hypochlorite concentration and 30 minutes soaking time could improved pH value (7. 70), whiteness (83.60 percent) organoleptic color test (5.04), and organoleptic odor test (4.20), while viscosity (17.85 cP), and reduced melanin content down to o. 05 percent.